The Effect of Profitability, Leverage, Liquidity, Capital Intensity, and Corporate Social Responsibility in Tax Avoidance - Ardiyanti, Ervina; Puspitasari, Elen (Golden Ratio of Taxation Studies, 2025)
Tax avoidance has emerged as a critical concern due to its potential impact on state revenue. This research investigates the influence of profitability, leverage, liquidity, capital intensity, and corporate social responsibility on tax avoidance. The study utilizes financial reports from manufacturing companies listed on the Indonesia Stock Exchange (IDX). Using the purposive sampling method, where the sample was selected based on several predetermined criteria, the research chose 63 company samples from a total population of 207. The study period spanned from 2021 to 2024. Data analysis was conducted using multiple linear regression, processed with IBM SPSS 25 software. The findings show that leverage significantly affects tax avoidance, where high debt produces interest rates that reduce tax burdens. Liquidity has a significant influence, as high liquidity increases tax avoidance through the flexibility of assets. In contrast, profitability, capital intensity, and corporate social responsibility do not have a significant effect on tax avoidance. The company manages strategic liquidity and leverage, prioritizes fiscal compliance, and strengthens CSR for long-term reputation, not just for tax purposes.